The Development of Learning Material of Nursery English Through Task Based Activities - Devi Windari; Busmin Gurning; Sri Minda Murni (Universitas Negeri Medan, 2014)
This research is aiming at 1) to know the existing phenomena of teaching and learning reading material of English for Nursery Purposes, 2) to find out kinds of reading materials of English for Nursery Purposes are needed by the students at STIKES Sari Mutiara, and 3) to find out a task-based learning reading materials of English for Nursery Purposes design. The research method used is research and development (R&D). The sources of the data are the students, the alumni, and the stakeholders whereas The targeted clients are the students of semester IV STKIES Sari Mutiara Medan. The instrument for collecting data are questionairre, documentation, and in depht interview. The data are analyzed by descriptive analysis.The results show that 1) in general the teaching learning is not optimal yet, particularly the learning materials are not relevant to the students and stakeholders’ need even the adequacy and availability are relatively adequate and available. 2) The students’ need in line with teaching learning reading is oriented in a student center learning, task activities, authentic reading materials, and strucutured essay test. and 3) the physical structure of learning materials consists of the following sections that is Preview, Getting Started, Orientation, Assessment, Related vocabulary Usages. Key Words: Reading Learning Material; Task based learning; and Nursery English